Experimental study on buoyancy and side friction of underground silos in sand and silty clay - Yang, Bo; Chen, Shaopeng; Zhang, Chengyao; Su, Na; Zhang, Shun; Zhu, Di (Frontiers in Earth Science, 2025)
In current anti-flotation designs for underground structures, buoyancy is typically calculated based on Archimedes’ principle and the contribution of side friction is often neglected, potentially resulting in unnecessary construction costs. In this study, a silo model with a vertically movable base was designed to conduct buoyancy tests under various water levels in both sand and silty clay. The attenuation pattern of groundwater buoyancy was analyzed, and the contribution of side friction to anti-flotation performance was also evaluated. The results indicate that: (1) Under the same water level, pore water pressure in sand was generally higher than that in silty clay, and with faster transmission and stabilization. (2) Buoyancy in sand was typically larger than that in silty clay at identical water level. Corresponding to the water levels of 65 cm, 70 cm, and 75 cm, the reduction coefficients of buoyancy were 0.87, 0.93, and 0.98 in sand, and 0.82, 0.89, and 0.94 in silty clay respectively. (3) The side friction acting on the silo model in sand was consistently lower than that in silty clay. The ratios of side friction to theoretical buoyancy in sand were 0.35, 0.32, and 0.25 at the water levels of 65 cm, 70 cm, and 75 cm, respectively; while in silty clay, the corresponding values were 0.47, 0.41, and 0.34. In practical engineering, it might be more rational to consider the reduction of buoyancy and the contribution of side friction, especially in weakly permeable soils such as silty clay, in the anti-flotation design of underground structures.